ANTI-CORRUPTION EDUCATION IN THE FAMILY, COMMUNITY, SCHOOL, AND STATE - Alil Rinenggo; Intan Kusumawati; Zaenul Stiyawan; Sutiyono Sutiyono (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This writing aims to describe the roles and strategies of the families, communities, schools, and state for anti-corruption education. Techniques for data collection was literature studies. The results of the study show that anti-corruption education in the family, school, community and state must be put into effects together. The role of the families is to educate children by example, habits, and dialogue. The employed strategy is to make use of the religion, society and culture, socialization and education, as well as the economy. People need to learn about corruption to improve the bureaucracy, understand their rights and obligations as smart and good citizens, and fully cooperate and commit. Schools need to design learning modules by developing anti-corruption values, such as core values, attitude values, and work ethic values. The strategy used by the school is to develop an environment-based anti-corruption PPKn learning model through cooperative learning. The state needs to implement a culture of shame in the government, include anti-corruption education in basic to higher education, and formulate social sanctions for corruption.